2015
DOI: 10.1038/srep11183
|View full text |Cite
|
Sign up to set email alerts
|

The first crop plant genetically engineered to release an insect pheromone for defence

Abstract: Insect pheromones offer potential for managing pests of crop plants. Volatility and instability are problems for deployment in agriculture but could be solved by expressing genes for the biosynthesis of pheromones in the crop plants. This has now been achieved by genetically engineering a hexaploid variety of wheat to release (E)-β-farnesene (Eβf), the alarm pheromone for many pest aphids, using a synthetic gene based on a sequence from peppermint with a plastid targeting amino acid sequence, with or without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
155
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(162 citation statements)
references
References 26 publications
4
155
1
2
Order By: Relevance
“…(Simpson et al, 2011;Blassioli-Moraes et al, 2013;Colazza et al, 2013). Considering these issues, one alternative is to manipulate the plants to produce and release specific volatiles, which can be done by classical breeding or genetic engineering (Schnee et al, 2006;Kunert et al, 2010;Michereff et al, 2011;Bruce et al, 2015). There is no example in the literature on this subject for transgenic transformed arable crops.…”
Section: The Potential To Apply Semiochemicals In Arable Crops To Attmentioning
confidence: 99%
“…(Simpson et al, 2011;Blassioli-Moraes et al, 2013;Colazza et al, 2013). Considering these issues, one alternative is to manipulate the plants to produce and release specific volatiles, which can be done by classical breeding or genetic engineering (Schnee et al, 2006;Kunert et al, 2010;Michereff et al, 2011;Bruce et al, 2015). There is no example in the literature on this subject for transgenic transformed arable crops.…”
Section: The Potential To Apply Semiochemicals In Arable Crops To Attmentioning
confidence: 99%
“…Cadenza was genetically engineered to emit (E)-β-farnesene using a synthetic gene based on a sequence from peppermint with a plastid targeting amino acid sequence, with or without a gene for biosynthesis of the precursor farnesyl diphosphate [40]. In the laboratory bioassay, volatiles from transformed plants were repellent to three species of cereal aphids and significantly enhanced the foraging behaviour of the parasitic wasp Aphidius ervi.…”
Section: Genetic Engineeringmentioning
confidence: 99%
“…In the laboratory bioassay, volatiles from transformed plants were repellent to three species of cereal aphids and significantly enhanced the foraging behaviour of the parasitic wasp Aphidius ervi. Although the laboratory studies demonstrated considerable potential for aphid control, field experiment during 2012/2013 cropping seasons did not show evidence of aphid repellence or increased parasitism under field conditions [40]. Modification of the experimental approach has been recommended to further test the promising laboratory results under realistic field conditions [40].…”
Section: Genetic Engineeringmentioning
confidence: 99%
See 2 more Smart Citations